Nerve Palsy following Total Hip Arthroplasty: A Review of the Current Literature - Salandra, Jonathan; Deliso, Marisa; Tang, Alex; Robbins, Conner J.; Rao, Juluru P. (The Journal of Hip Surgery, 2022)
The incidence of postoperative nerve palsy following total hip arthroplasty (THA) is reported to be 1 to 2%. The most common injury is to the sciatic nerve, but other nerve palsies including the femoral, obturator, and pudendal nerves, have been implicated. There is also an increased risk of nerve palsy following THA in female patients, those who undergo revision procedures, and those with a previous history of developmental hip dysplasia. The prognosis for recovery for each nerve palsy is directly correlated to the extent of nerve damage. Prevention is always the best form of treatment for these conditions, and one method by which this may be accomplished is through electromyography and other variations of intraoperative observation.
Keywords: total hip arthroplasty; nerve palsy; postoperative; review